2007
DOI: 10.1038/oby.2007.306
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Mexican‐American Children Following a Weight Management Program

Abstract: FOREYT. Quality of life in Mexican-American children following a weight management program. Obesity. 2007;15:2553-2556. Objective: The objective was to evaluate quality of life (QOL) in at-risk-for-overweight and overweight MexicanAmerican children after participating in 6 months of intensive weight management or self-help. Research Methods and Procedures: Eighty sixth-and seventh-grade at-risk-for-overweight (BMI Ն85th to Ͻ95th percentile) and overweight (BMI Ն95th percentile) Mexican-American children were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
57
3
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 17 publications
5
57
3
3
Order By: Relevance
“…15 These studies documented significant improvements in HRQOL with weight loss, but pooling data to examine a possible quantitative relationship for the purposes of the present review was not possible as these studies assessed changes in weight status differently (see Table 2) and few utilized common tools to assess HRQOL. 21,35 Fullerton et al 21 found that improvements in BMI z-scores explained significant changes in physical functioning (b ¼ À0.22, Po0.005), but not psychosocial functioning after a 12-week behavioral therapy intervention (Table 2). Knopfli et al 36 reported improvements in all subsets of HRQOL in severely obese adolescents with a median BMI reduction of 5 kgm -2 after an 8-week inpatient program.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…15 These studies documented significant improvements in HRQOL with weight loss, but pooling data to examine a possible quantitative relationship for the purposes of the present review was not possible as these studies assessed changes in weight status differently (see Table 2) and few utilized common tools to assess HRQOL. 21,35 Fullerton et al 21 found that improvements in BMI z-scores explained significant changes in physical functioning (b ¼ À0.22, Po0.005), but not psychosocial functioning after a 12-week behavioral therapy intervention (Table 2). Knopfli et al 36 reported improvements in all subsets of HRQOL in severely obese adolescents with a median BMI reduction of 5 kgm -2 after an 8-week inpatient program.…”
Section: Resultsmentioning
confidence: 98%
“…6,14,[17][18][19][20] Six studies utilized weight loss interventions (Table 2), of which two were randomized controlled trials (RCTs). 21,22 One paper reported two studies (cross-sectional and intervention) and was therefore included in both the tables. 15 Fifteen studies utilizing the PedsQL were included in the pooled analyses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Porém, é possível que programas de redução de peso melhorem a qualidade de vida dessas crianças, especialmente no domínio físico 27 .…”
Section: Discussionunclassified